The image of Iraqi political parties to the public and its relationship to the public's participation in the legislative elections - Faris, Faris Ismail; Abdul Rahman, Iman (Al-Adab Journal, 2021)
Faris Ismail Faris. The image of Iraqi political parties among the public and its relationship to their participation in the legislative elections. Research extracted from a PhD thesis, University of Baghdad, College of Mass Communication, Department of Radio and Television Journalism, 2020.One of the most important influences observed by the researcher is the image that satellite channels create among the public about political parties and blocs and their impact on the behavior of voters in the elections, meaning that the relationship between individuals and the process of forming a political image, which pushes them to political participation, does not complete its set objectives without achieving the required response from them. Through the media, especially the news media, as news plays a major role in transmitting information about it to the recipients, and it is usually allocated extensive coverage to it through intended treatments for a number of its topics and events, which the contact person chooses according to the policy of the institution and those in charge of it, it was natural for the researcher to turn To its importance as a programmatic quality that deserves to be studied in order to understand its effects and capabilities in shaping the image of the public towards participation in the elections in light of the news frameworks theory, which has become influential in shaping images and changing behavior and practices.This study aims to explore “what is the relationship of the image formed by satellite channels among the public with their participation in the legislative elections”, using the researcher in his study of the survey method, and the questionnaire form tool. The questionnaire questions included the characteristics of the sample and the nature of its exposure to news bulletins, as well as the image formed among the public, and the research reached Several results can be summarized as follows:The researcher found that all respondents are exposed to news bulletins, but their viewing patterns are different, and the majority of them answered (I watch them daily). The researcher concludes from this that the traditional means are appreciated and interested by some respondents, as they are keen to follow the news through their favorite channels in order to be reassured of the validity of the information. They are drawn from the daily events and issues, and this indicates that most of the study sample are keen to regularly follow the news releases on Iraqi satellite channels.The researcher found that the majority of respondents prefer to watch Al-Sharqiya channel to follow news bulletins, and the researcher concludes that the public prefers to follow the news of political parties and blocs on Al-Sharqiya channel. For the parties and the government.The researcher found that the majority of the respondents find that the image that satellite channels try to form about political parties and blocs is the "negative image", since this paragraph formed the largest percentage, and the reason for this is that the channels entrench the negative image in the minds of the public by conveying the news and framing it in negative frameworks. .The researcher found that most of the respondents prefer not to participate in future elections by following up on private news, parties (candidates) and political blocs, as the percentage of the paragraph (I don’t know, no) has increased since these paragraphs formed the largest percentage, and the reason for this is the respondents ’lack of confidence in the parties. Participation in the elections, as well as the consolidation of negative images of the parties in the minds of the public, and thus their access to the belief that participation is useless.